2016
DOI: 10.3389/fpsyg.2015.01981
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual-Cognitive Changes During Motor Learning: The Influence of Mental and Physical Practice on Mental Representation, Gaze Behavior, and Performance of a Complex Action

Abstract: Despite the wealth of research on differences between experts and novices with respect to their perceptual-cognitive background (e.g., mental representations, gaze behavior), little is known about the change of these perceptual-cognitive components over the course of motor learning. In the present study, changes in one’s mental representation, quiet eye behavior, and outcome performance were examined over the course of skill acquisition as it related to physical and mental practice. Novices (N = 45) were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 58 publications
4
65
0
Order By: Relevance
“…On the questionnaire, they indicated on sixpoint Likert scales (1 = very difficult, 6 = very easy) how easy it was to follow the instructions and how easy it was to imagine the movements involved in the tennis serve. In addition, they were asked to mention any problems they experienced during training (Frank et al, 2016).…”
Section: Manipulation Checkmentioning
confidence: 99%
See 1 more Smart Citation
“…On the questionnaire, they indicated on sixpoint Likert scales (1 = very difficult, 6 = very easy) how easy it was to follow the instructions and how easy it was to imagine the movements involved in the tennis serve. In addition, they were asked to mention any problems they experienced during training (Frank et al, 2016).…”
Section: Manipulation Checkmentioning
confidence: 99%
“…They found that practice led to an improvement in performance that was accompanied by functional changes in mental representation structures. Similarly, mental representations have been found to change functionally with mental practice such as imagery (Frank et al, , 2016(Frank et al, , 2018bSimonsmeier et al, 2018) and observation (Frank et al, 2018a) as well as in the context of expertise (e.g., Schack and Mechsner, 2006) and rehabilitation (Braun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Between 1998 and 2009, he was 11 years the number one in the official world golf ranking. Among others, his exceptional performance in putting can be attributed to his QE on the CISS 1 (2016) October 2016 I Article 108 I 3 green (Frank, Land, & Schack, 2016;Vickers, 1992). Over an exceptionally long time, Tiger Woods was able to outperform other golf players.…”
Section: Visual Expertise Changes As the Social Context Changesmentioning
confidence: 99%
“…From this point of view, it might be the effect anticipation based on the effect representation available that is reflected by the QE. Recent research indicates that the representational networks of a motor action develop alongside of the QE during learning (Frank, Land, & Schack, 2016). Participants trained on a golf putting task over the course of three days.…”
Section: A Perceptual-cognitive Approach To the Qementioning
confidence: 99%
“…It is therefore surprising that our insight into its functioning, into the underlying mechanisms of the QE, has remained scarce to date. While research on the QE has grown, covering cross-sectional research designs (e.g., expert novice paradigm with QE as dependent variable; e.g., Vickers, 1992) as well as longitudinal research designs (e.g., learning paradigm with QE Citation: Frank, C., & Schack, T. (2016). In my mind's (quiet) eye: a perceptual-cognitive approach to the Quiet Eye -comment on Vickers.…”
Section: Introductionmentioning
confidence: 99%